2004
DOI: 10.4049/jimmunol.172.6.3553
|View full text |Cite
|
Sign up to set email alerts
|

Heme Oxygenase-1 Modulates the Expression of Adhesion Molecules Associated with Endothelial Cell Activation

Abstract: Heme oxygenase-1 (HO-1) cleaves the porphyrin ring of heme into carbon monoxide, Fe2+, and biliverdin, which is then converted into bilirubin. Heme-derived Fe2+ induces the expression of the iron-sequestering protein ferritin and activates the ATPase Fe2+-secreting pump, which decrease intracellular free Fe2+ content. Based on the antioxidant effect of bilirubin and that of decreased free cellular Fe2+, we questioned whether HO-1 would modulate the expression of proinflammatory genes associated with endothelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
281
4
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 419 publications
(322 citation statements)
references
References 49 publications
25
281
4
6
Order By: Relevance
“…29 In endothelial cells, modulation of HO-1 activity by Nrf2 inhibited NF-kBemediated transcription of vascular cell adhesion molecule-1 and E-selectin. 40 Induction of Nrf2 signaling in mouse peritoneal macrophages reduces lipopolysaccharide-mediated induction of cyclooxygenase 2, tumor necrosis factor-a, and IL-1b expression. 41 In response to acute lung injury, deletion of Nrf2 was associated with impaired resolution of inflammation.…”
Section: Nrf2 In Cellular Redox Homeostasismentioning
confidence: 99%
“…29 In endothelial cells, modulation of HO-1 activity by Nrf2 inhibited NF-kBemediated transcription of vascular cell adhesion molecule-1 and E-selectin. 40 Induction of Nrf2 signaling in mouse peritoneal macrophages reduces lipopolysaccharide-mediated induction of cyclooxygenase 2, tumor necrosis factor-a, and IL-1b expression. 41 In response to acute lung injury, deletion of Nrf2 was associated with impaired resolution of inflammation.…”
Section: Nrf2 In Cellular Redox Homeostasismentioning
confidence: 99%
“…7,8 In order to assess if ARE-driven HO-1 expression can have antiinflammatory effects in endothelial cells, we first examined its effect on NF-kB activation assessed by the activation of the NF-kB-regulated luciferase-reporter construct. To this end, cells were transduced with either an empty lentiviral control vector having only the phosphoglycerate kinase (PGK) promoter but no transgene, or 2 Â GCLM-HO-1 vector together with the NFkB-luciferase-reporter construct.…”
Section: Lentiviral Transduction Of Are-ho-1 Decreases the Induction mentioning
confidence: 99%
“…In endothelial cells, adenoviral overexpression of HO-1 has been shown to inhibit tumor necrosis factor (TNF)-a-induced activation of nuclear factor (NF)-kB and vascular cell adhesion molecule-1 (VCAM-1) expression. 7,8 For an optimal therapeutic response, it would be beneficial if the transgene expression could be regulated in order to turn the gene expression on and off when needed. This can be accomplished through the use of promoters that can be activated by orally administered drugs, such as tetracycline.…”
Section: Introductionmentioning
confidence: 99%
“…48 Indeed, numerous recent observations point to a potential role of HO-1 in the downregulation of proinflammatory cytokine expression at the site of inflammation in various model systems. [49][50][51][52][53] It has also been shown that HO-1 might provide an anti-inflammatory action in vivo through the downmodulation of cell adhesion molecules accompanied by inhibition of leukocyte infiltration, [54][55][56] and via promotion of noninflammatory angiogenesis facilitating tissue repair. 56 Moreover, an increased leukocyte adhesion to the vascular wall and spontaneous perivascular infiltration of leukocytes in various tissues of HO-1-deficient mice has been reported before.…”
Section: Expression Of Il-6 After To Administration and Its Possible mentioning
confidence: 99%